Evaluation of the eOSCE for testing clinical skills - Berendes, Svenja; Schaper, Elisabeth; Tipold, Andrea; Wissing, Sandra (Frontiers in Veterinary Science, 2023)
The OSCE is a proven instrument for testing practical skills of students, not only in the (veterinary) medical field. At the University of Veterinary Medicine Hannover, Foundation (TiHo), students must complete a 10week rotation in one of the university's own clinics during the practical year in the 9th and 10th semesters in addition to other practical training. Within this framework, the first training for acquiring clinical practical skills with a formative examination (OSCE; Objective Structured Clinical Examination) was developed in the Clinical Skills Lab (CSL) in 2014. Since 2018, the TiHo has been the first veterinary medical training institution in Germany to conduct electronic OSCEs (eOSCEs). In the future, eOSCEs will also be introduced as a summative examination at the TiHo. For this reason, students in the practical year of the winter semester 2021/2022 and summer semester 2022 as well as former and current examiners were surveyed regarding their satisfaction with the eOSCE examination format as part of this study. The 175 analyzed questionnaires from students and 27 analyzed questionnaires from examiners showed a high level of satisfaction with the eOSCE overall, but at the same time indicated problems that should be ironed out before it is introduced as a summative examination in the state examination. In addition to its standardization and objectivity, the examination format also convinced with its quality-assurance review procedure and the direct feedback possibility with regard to the students' performance.